In vivo study of the antihypertensive effect of bidara leaf (Ziziphus spina-christi) during pregnancy - Dilla, Tasya Nurlaila; Hadisaputro, Suharyo; Santjaka, Aris (MEDISAINS, 2021)
Background: Bidara is drought tolerant and very easy to grow in tropical climates such as Indonesia. Bidara contains a combination of calcium, potassium, and magnesium, and active flavonoid compounds, and antioxidant activity that play a role in inhibiting free radical damage, improving endothelial function so that it can potentially lower blood pressure. Previous studies explained that a dose variant of no more than 300mg/kg BW is beneficial while minimizing pathological changes. However, there has been no research related to the effect of bidara leaf in lowering blood pressure, so it is necessary to do related research.Objective: Analyze the effect of bidara leaf extract at a 200 mg/kg BW dose and 300 mg/kg BW on systolic and diastolic blood pressure.Methods: 24 pregnant female Wistar rats induced hypertension, aged 6-8 weeks with a weight of 130-230 grams. The rats were randomized so that they consisted of 2 control groups and two experimental groups, which were given various doses of bidara leaf for nine days. Blood pressure was measured using non-invasive CODA.Results: The blood pressure of rats in the bidara leaf extract group at doses of 200mg/kg BW and 300mg/kg BW decreased systolic and diastolic compared to the control group (p<0.05). The 200mg/kg BW dose group experienced a decrease in blood pressure of 12.3% for systolic and 16.32% for diastolic; the 300mg/kg BW dose group experienced a decrease in blood pressure of 19.99% for systolic and 27.73% for diastolic.Conclusion: Bidara leaf extract can reduce the blood pressure of pregnant rats with hypertension.